2013
DOI: 10.1590/s0100-204x2013000800051
|View full text |Cite
|
Sign up to set email alerts
|

Larvicultura de tilápia em água doce e água salinizada

Abstract: Resumo -O objetivo deste trabalho foi avaliar o efeito de diferentes salinidades da água na larvicultura de tilápia. Larvas com cinco dias pós-eclosão foram estocadas em tanques de 6 L durante 30 dias. Os tratamentos experimentais foram água doce e água com 2, 4, e 6 g L -1 de sal, com seis repetições. As larvas mantidas a 6 g L -1 de sal apresentaram mortalidade total, antes de dez dias de alimentação ativa. Na salinidade a 4 g L -1 , a sobrevivência e o desempenho foram inferiores aos registrados para os ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 14 publications
0
15
0
Order By: Relevance
“…A salinity of 2 g of salt L −1 had been previously used for the species for the first 10 days of feeding with Artemia (Jomori et al., 2013). This salinity also has been beneficial in the larviculture of other freshwater species such as H. lacerdae (Luz & Portella, 2002), L. alexandri (Luz & Santos, 2008; Nascimento et al., 2020; Santos & Luz, 2009), P. coruscans and P. costatus (Santos & Luz, 2009), R. aspera (Luz & Santos, 2010), P. mesopotamicus (Jomori et al., 2012), A. ocellatus and B. amazonicus (Jomori et al., 2013), O. niloticus (Luz et al., 2013), Pterophyllum scalare and Heros severus (Eiras et al., 2019), B. splendens (Fabregat et al., 2017), and B. vonoi (Coraspe‐Amaral et al., 2017), showing it to be a great alternative for intensive larviculture of freshwater fish.…”
Section: Discussionmentioning
confidence: 99%
“…A salinity of 2 g of salt L −1 had been previously used for the species for the first 10 days of feeding with Artemia (Jomori et al., 2013). This salinity also has been beneficial in the larviculture of other freshwater species such as H. lacerdae (Luz & Portella, 2002), L. alexandri (Luz & Santos, 2008; Nascimento et al., 2020; Santos & Luz, 2009), P. coruscans and P. costatus (Santos & Luz, 2009), R. aspera (Luz & Santos, 2010), P. mesopotamicus (Jomori et al., 2012), A. ocellatus and B. amazonicus (Jomori et al., 2013), O. niloticus (Luz et al., 2013), Pterophyllum scalare and Heros severus (Eiras et al., 2019), B. splendens (Fabregat et al., 2017), and B. vonoi (Coraspe‐Amaral et al., 2017), showing it to be a great alternative for intensive larviculture of freshwater fish.…”
Section: Discussionmentioning
confidence: 99%
“…Larviculture is one of the critical phases of production in captivity and considered the bottleneck in fish production because it encompasses several changes during larval development (Dabrowski & Portella, 2005; Portella & Dabrowski, 2008; Portella et al., 2012), such as alterations in feeding management, water parameters and other stress‐related factors (Abe et al., 2019; Couto et al, 2018; Fabregat et al., 2017; Hui et al., 2019; Luz et al, 2013; Santos & Luz, 2009; Souza et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Salt can also be used for disease prevention (Németh et al, 2013); moreover, it can reduce the toxic effects of nitrogenous compounds (Sampaio et al, 2002), which are common in RASs. Thus, the brackish water has been used for freshwater fish with satisfactory results (Sampaio et al, 2002;Luz et al, 2013;Jomori et al, 2013;Németh et al, 2013). Studies on many species of fish have shown that the addition of 2 g L -1 salt improves fish performance and survival (Santos & Luz, 2009;Luz et al, 2012Luz et al, , 2013Jomori et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the brackish water has been used for freshwater fish with satisfactory results (Sampaio et al, 2002;Luz et al, 2013;Jomori et al, 2013;Németh et al, 2013). Studies on many species of fish have shown that the addition of 2 g L -1 salt improves fish performance and survival (Santos & Luz, 2009;Luz et al, 2012Luz et al, , 2013Jomori et al, 2013). The last mentioned authors also associated the beneficial effects of salt with the energy expenditure required by the ionic and osmotic regulation, which is higher in freshwater than in salt water; their studies evaluated the use of salinized water for the production of freshwater fish and UV for disinfection.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation